The role of double volume exchange transfusion in the management of severe hyperbilirubinemia while on extracorporeal life support in neonates: a case report - Dalldorf, Katherine; Juliano, Courtney; Dawa, Tenzin; Ratner, Veniamin; Tiozzo, Caterina (Frontiers in Pediatrics, 2025)
Extracorporeal membrane oxygenation (ECMO) related hemolysis is a severe complication seen frequently in neonates requiring ECMO support. While circuit exchange is a common management approach, it carries the risk of hemodynamic instability due to the inflammatory reaction triggered by exposure to a new circuit. We present the case of a newborn with remarkably elevated bilirubin levels that persisted despite circuit changes and responded to a double volume exchange transfusion (DVET) while under extracorporeal life support (ELS). This is the first reported occurrence of a DVET performed on a newborn with severe hemolysis while on veno-arterial ELS and only the second documented case in a pediatric patient. Our aim is to underscore the feasibility and safety of utilizing DVET for newborns undergoing ELS. This procedure serves as an alternative or adjunct approach to circuit replacement for the management of severe hemolysis and associated hyperbilirubinemia.